2019
DOI: 10.1111/dom.13691
|View full text |Cite
|
Sign up to set email alerts
|

The importance of dyslipidaemia in the pathogenesis of cardiovascular disease in people with diabetes

Abstract: Atherosclerotic cardiovascular events are the leading cause of mortality and morbidity in those with diabetes. A key contributor to the development of atherosclerosis in this population is the presence of a particularly atherogenic lipid profile often referred to as ‘Diabetic Dyslipidemia’. This profile is characterized by elevated triglycerides, triglyceride‐rich lipoproteins, small dense LDL particles, and reduced HDL levels. This article reviews the underlying aetiology and pathophysiology of this dyslipida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 126 publications
(217 reference statements)
0
14
1
1
Order By: Relevance
“…Dyslipidemia is described as an abnormal level of circulating lipids. It has been acknowledged that dyslipidaemia increases the risk of cardiovascular disease development [ 69 ]. This condition may be of primary cause (genetic) or secondary (diet, drugs, chronic diseases, and metabolic disorders, including MetS).…”
Section: Ca Vs Dyslipidemiamentioning
confidence: 99%
“…Dyslipidemia is described as an abnormal level of circulating lipids. It has been acknowledged that dyslipidaemia increases the risk of cardiovascular disease development [ 69 ]. This condition may be of primary cause (genetic) or secondary (diet, drugs, chronic diseases, and metabolic disorders, including MetS).…”
Section: Ca Vs Dyslipidemiamentioning
confidence: 99%
“…The causal role of high cholesterol concentrations in the pathogenesis of chronic conditions is well established. Obesity and insulin resistance are linked to alterations in the lipoprotein particle profile and this may influence type 2 diabetes and cardiovascular disease (CVD) risk [2][3][4]. Traditional lipid tests quantify the cholesterol or triglyceride content of lipoproteins, and the amount of cholesterol carried by lipoprotein particles is thought to be an important parameter for estimating disease risk [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is characterised by elevated levels of TGs, TG-rich lipoproteins, small dense LDL particles, and reduced HDL levels. 13 Lipid modification to reduce CVD events Normally, most cholesterol is carried in low-density lipoprotein cholesterol (LDL-C) and there is a strong, graded, positive association between total and LDL-C, and the risk of CVD over a wide range of plasma cholesterol concentrations. 14,15 There is unequivocal evidence that reducing plasma LDL-C reduces CVD risk, and various trials and epidemiological studies, with and without statins, using angiographic or clinical endpoints, have confirmed that the reducing LDL-C is also key component in preventing CVD.…”
Section: Trends In Urology and Men's Healthmentioning
confidence: 99%
“…People with diabetes have a particularly atherogenic lipid profile (diabetic dyslipidaemia), which is a key contributor to the development of atherosclerosis. This is characterised by elevated levels of TGs, TG‐rich lipoproteins, small dense LDL particles, and reduced HDL levels 13 …”
Section: Diabetes and Cvdmentioning
confidence: 99%